Atlas of marine zooplankton Straits of Magellan (Amphipods, Euphausiids, Mysids, Ostracods, and chaetognats - GUGLIELMO; L. IANORA, A. (Springer-Verlag Berlin Heidelberg New York, ISBN 3-540-58678-4, 1995)
M1182
NeMys doc_id: 3518